A study of the association of prenatal inflammatory diet and adverse infant birth outcomes in a birth cohort in Uganda - Ndlovu, Davies (Department of Public Health and Family Medicine, 2023)
Background: Low birth weight (LBW) and low infant lung capacity among others are risk factors for childhood and adulthood chronic respiratory diseases such as chronic obstructive pulmonary disease (COPD) and asthma. These respiratory diseases are among the leading causes of death and disability worldwide. The aetiology of these respiratory diseases and other inflammatory conditions has recently been linked to maternal diet during pregnancy. As such it has been important to study the role of maternal diet during pregnancy to find any association with maternal and infant outcomes. Highly diverse diets have been thought to be a proxy to maternal nutrient adequacy as well as healthy diet. Diverse diets may offer protection from inflammatory airway diseases and other inflammatory diseases by evening out inflammatory and anti-inflammatory food components. Purpose: To investigate the effect of Dietary diversity (DD) and Dietary inflammatory index (DII), on infant birth outcomes particularly birth weight and lung function and to determine if there is any association. Methods: In this study we analysed data obtained from 564 women who attended antenatal care facilities in Kalungu district of rural Uganda. These women were recruited by convenience sampling as they walked into the facilities for antenatal care. Those who gave consent were asked about their diets and socioeconomic statuses by means of questionnaires. Infant outcomes were measured by healthcare professionals at presentation for postnatal care at 6 weeks ofage. Dietary scores were created as the number of unique food groups obtained from the data collected. The scores ranged from 0-14, with 14 representing those who consumed all 14 unique food groups identified in the study. Dietary inflammatory index was also calculated from the data obtained. The methods for calculating the DII will be explained in detail under methods. The data collection for this purpose was based on 24hr recall. Results: The mean Dietary Diversity score was 4.61 +/- 1.79 SD. In the previous 24 h, 84.8% of the participating women had consumed tubers such as cassava, 57.1% reported consuming grains or cereal, 12.6% vegetables, 19.3% Fruits, 1.2% meat and 7.4% eggs. There were statistically significant differences in dietary practices of the women according to their level of education, with 81% of those who attained tertiary education having adequate dietary diversity. Starches were the most consumed food group with an average of 16 servings per week while meat, processed starches (samosas, etc), fruits and vegetables were consumed at=<2 serving per week, with meat the least consumed at an average of less than 1 serving per week. Although marginal, the diets of the participants were mostly anti-inflammatory with an average dietary inflammatory score of -1.2. Those with the lowest inflammatory score were associated with more servings of legumes, green leafy vegetables, fish and less servings of processed starches and animal oil. There was no association observed between dietary diversity and infant birth outcomes, birth weight and lung function. No association was also observed between Dietary inflammatory scores and infant lung function.